Effects of PVA-GTA-I radiochromic gel dosimeter components on optical dose-response. Issue 1 (1st January 2022) - Hayashi, Shin-ichiro; Ono, Kaoru; Fujino, Keisuke; Kurihara, Ryosuke
Abstract: In recent years, a novel radiochromic gel dosimeter was developed that utilizes the color development of a polyvinyl alcohol-iodide (PVA-I) complex. In this study, we explore the effects of different iodide salts (LiI, NaI, KI, CsI, NH4 I, CaI2, and ZnI2 ) and PVAs with different degrees of polymerization (500, 1000, and 1500) and saponification (80, 88, and 98 mol%) were investigated on a PVA-GTA-I gel dosimeter using PVA that was chemically crosslinked with glutaraldehyde (GTA) as a matrix. The results showed that these substitutions had negligible effect on dose-responses, such as sensitivity and dose-rate independence.